The Temple scroll and the Bible : the methodology of 11QT - Swanson, Dwight D. (Studies on the Texts of the Desert of Judah, 1995)
That the Temple Scroll is re-written Torah is recognised, but discussion of how the Torah is used has been hampered by absence of detailed analysis of the Scroll. This volume addresses this lack by careful examination of major portions of the Scroll. Representative portions of each division of the Scroll are analyzed, first to establish precisely which biblical texts are used, and then to show how these texts are placed in relation to each other. From this study, a specific editorial methodology is uncovered. The final chapter summarises the conclusions and discusses implications for wider Qumran studies. This book provides data essential not only to further the discussion on the exegetical methodology of this Scroll, but also for insight into the transition from "inner-biblical" exegesis to rabbinic commentary.